THE EFFECTIVENESS OF E-LAB TO IMPROVE GENERIC SCIENCE SKILLS AND UNDERSTANDING THE CONCEPT OF PHYSICS - Siswanto, J.; Saefan, J.; Suparmi, S.; Cari, C. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2016)
The aimed of this sudy are: (1) investigate the effectiveness of E-Lab to improve generic science skills and understanding the concepts oh physics; and (2) investigate the effect of generic science skills towards understanding the concept of students after learning by using the E-Lab. The method used in this study is a pre-experimental design with one group pretest-posttest. Subjects were students of Physics Education in University PGRI Semarang with methode random sampling. The results showed that: (1) learning to use E-Lab effective to increase generic science skills of students; and (2) Generic science skills give positive effect on student conceptual understanding on the material of the photoelectric effect, compton effect, and electron diffraction. Tujuan penelitian ini yaitu: (1) menyelidiki efektifitas E-Lab untuk meningkatkan keterampilan generik sains dan pemahaman konsep mahasiswa; dan (2) menyelidiki pengaruh keterampilan generik sains terhadap pemahaman konsep mahasiswa setelah dilakukan pembelajaran dengan menggunakan E-Lab. Metode penelitian yang digunakan dalam penelitian ini adalah pre-experimental dengan desain one group pretest-posttest. Subjek penelitian adalah mahasiswa Program Studi Pendidikan Fisika Universitas PGRI Semarang, dengan metode pengambilan sampel penelitian secara random. Hasil penelitian menunjukkan bahwa bahwa: (1) pembelajaran menggunakan E-Lab efektif untuk meningkatkan keterampilan generik sains mahasiswa; dan (2) Keterampilan generik sains berpengaruh positif terhadap pemahaman konsep mahasiswa pada materi efek fotolistrik, efek compton, dan difraksi elektron.